Deformation of lamellar TiAl alloys by longitudinal twinning. (June 2016) - Edwards, Thomas Edward James; Di Gioacchino, Fabio; Muñoz-Moreno, Rocío; Clegg, William John
Abstract: The occurrence of longitudinal twinning in the engineering alloy Ti-45Al-2Nb-2Mn (at.%)-0.8 vol.% TiB2 has been studied by measuring the changes in crystallographic orientation within individual lamellae during microcompression. Twinning in this alloy appeared to be a nucleation-limited process with the twins growing from lamellar boundaries at resolved shear stresses as low as 100 MPa, consistent with observations elsewhere. However, instead of forming twins ~ 10–200 nm in thickness, as in polysynthetically twinned crystals, the longitudinal twins in this alloy were initiated at a lamellar boundary and then spread through the whole lamella. Graphical abstract: